Evaluating Student Investment Interest Amidst Financial Technology Ease - Astari, Gusti Ayu Shinta Dwi; Wijaya, Bagus Kusuma (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
The emergence of investment features within Fintech ecosystems has democratized access to capital markets for Generation Z. However, empirical evidence suggests a disconnect between accessibility and actual investment participation. This study aims to analyze the gap between investment interest (intention) and actual investment behavior (action) among university students. Employing a descriptive quantitative method with 30 respondents, the research investigates the determinants of low investment uptake despite high digital fluency. The findings reveal a significant "Intention-Behavior Gap": while 85% of respondents expressed a strong desire to invest, only 23% actively utilize investment features. The primary barriers identified are not capital constraints, but rather low "Risk Literacy" and "Herding Behavior" where students rely on influencers rather than fundamental analysis. The study concludes that technological ease without fundamental financial education triggers "Fear of Missing Out" (FOMO) rather than rational investment decision-makin.